Interaction of Insecticides and Fungicides in Bees - Schuhmann, Antonia; Schmid, Anna Paulina; Manzer, Sarah; Schulte, Janna; Scheiner, Ricarda (Frontiers in Insect Science, 2022)
Honeybees and wild bees are among the most important pollinators of both wild and cultivated landscapes. In recent years, however, a significant decline in these pollinators has been recorded. This decrease can have many causes including the heavy use of biocidal plant protection products in agriculture. The most frequent residues in bee products originate from fungicides, while neonicotinoids and, to a lesser extent, pyrethroids are among the most popular insecticides detected in bee products. There is abundant evidence of toxic side effects on honeybees and wild bees produced by neonicotinoids, but only few studies have investigated side effects of fungicides, because they are generally regarded as not being harmful for bees. In the field, a variety of substances are taken up by bees including mixtures of insecticides and fungicides, and their combinations can be lethal for these pollinators, depending on the specific group of insecticide or fungicide. This review discusses the different combinations of major insecticide and fungicide classes and their effects on honeybees and wild bees. Fungicides inhibiting the sterol biosynthesis pathway can strongly increase the toxicity of neonicotinoids and pyrethroids. Other fungicides, in contrast, do not appear to enhance toxicity when combined with neonicotinoid or pyrethroid insecticides. But the knowledge on possible interactions of fungicides not inhibiting the sterol biosynthesis pathway and insecticides is poor, particularly in wild bees, emphasizing the need for further studies on possible effects of insecticide-fungicide interactions in bees.